Evaluation and driving force analysis of ecological quality in Central Yunnan Urban Agglomeration - Li, Yimin; Li, Yuanting; Yang, Xue; Feng, Xianjie; Lv, Shengbin (Ecological indicators, 2024)
•The modified RSEI is more suitable for the evaluation of ecological quality in CYUA.•The ecological status of CYUA shows an improving trend and is better in western part.•Vegetation, climate and human activities are important in altering ecological quality.•The projections indicate that MRSEI of CYUA will continue to improve in 2025 and 2029. To promote the sustainable development of the karst region, investigating the spatial–temporal evolution of ecological quality and elucidating key influencing factors is significant. The study quantified the ecological quality of Central Yunnan Urban Agglomeration (CYUA) from 2002 to 2021 using Google Earth Engine (GEE) and the Modified Remote Sensing Ecological Index (MRSEI) with soil erosion indicators. Additionally, the study analyzed MRSEI's spatial distribution, spatial–temporal transfer, and driving factors by integrating the Sen + Mann-Kendall trend test and the grey correlation degree. The grey prediction model GM (1,1) and CA-Markov model were employed to predict CYUA's future ecological condition in terms of MRSEI's mean value and spatial distribution of MRSEI rank. Results indicate that: (1) Greenness and humidity significantly enhanced the ecological environment, while dryness, heat, and soil erosion indicators had the opposite effect. The first principal component, with a mean contribution of 70.20 % across 2002, 2007, 2012, 2017, and 2021, indicated that MRSEI based on PC1 was suitable for evaluating CYUA's ecological quality. (2) Spatially, the western CYUA generally outperformed the eastern part in terms of ecological quality, with the moderate class dominating the ecological quantity. Temporally, CYUA's holistic ecological condition consistently improved between 2002 and 2021. (3) Regional height, climatic conditions, and human construction projects were key factors altering ecological quality, as evidenced by the top five MRSEI influencing factors: greenness, humidity, normalized difference impervious surface index, elevation, and average annual rainfall. (4) Forecast results suggest that areas classified as good or excellent are expected to exceed 30 % by 2029, indicating ongoing and future improvements in CYUA's ecological quality. This study serves as a reference for ecological protection and regional sustainability in karst region.